Técnicas de produção de açúcar no Brasil colonial: as edições do livro Cultura e opulência do Brazil - Medeiros, Andréia Medolago de (2012)
Sugar production in Brazil begins with occupation of the colony and during the 18th Century is one of the most important activities developed in Brazil. The lack of investment and high charges levied by Portugal, in addition to the restrictions on the press have hampered innovations. The only published work in Brazil dedicated to main items produced in Brazil sugar, tobacco and gold is made by Antonil, titled Culture and Opulence of Brazil: for its drugs and mines, being collected and burned shortly after its publication. With the creation of the Literary Home of Arco do Cego, Frei Veloso dedicates a series of works devoted to agricultural improvement, many of which related to the sugar production. It is in this context that, in 1800, Veloso republished partially the work of Antonil, adding to it an appendix with the indication of a new milling. In this work we will expose the techniques used in the sugar production, throughout the 18th century in Brazil, seeking, on the one hand, studying the methods of sugar production and, on the other hand, to analyze the possible changes in techniques, arising from the need to improve the yield of the sugar from the mills of Pernambuco, in the early 19th century